The Role of Vitamin D in Kidney Transplantation Outcomes: A Systematic Review - Georgios Koimtzis; Leandros Stefanopoulos; Verity Brooker; Georgios Geropoulos; Christopher G. Chalklin; Sapna Gupta; Eliot Carrington-Windo; Maria Papaioannou; Theodosios S. Papavramidis (Life, 2022)
The aim of this systematic review is to assess the impact of vitamin D on the outcomes of kidney transplantation and investigate whether its deficiency is associated with a negative impact. Methods: We conducted a systematic literature search in PubMed, Scopus and Cochrane databases, as well as gray literature. Ultimately, 16 articles with an average of 255.75 patients were included in this review. These articles compared the long-term outcomes of vitamin D deficiency and/or vitamin D supplementation therapy on kidney transplant recipients by assessing various parameters. Results: Most of the included studies showed a negative effect of vitamin D deficiency on kidney transplantation by being associated with a worse graft function, higher incidence of acute rejection episodes, higher incidence of proteinuria and lower overall graft and patient survival rate. Conclusions: We suggest that patients awaiting kidney transplantation have a careful evaluation in order to assess their vitamin D status and the optimal supplementation therapy. Regular follow-up of vitamin D levels post-transplant is also suggested. Prospective studies will be needed to establish the positive effects of vitamin D supplementation therapy on kidney transplant outcomes.